The Ethics of Withdrawing Artificial Food and Fluid from Terminally Ill Patients: an end-of-life dilemma for Japanese nurses and families - Konishi, Emiko (Nursing ethics, 2002)
End-of-life issues have become an urgent problem in Japan, where people are among the longest lived in the world and most of them die while connected to high-technology medical equipment. This study examines a sensitive end-of-life ethical issue that concerns patients, families and nurses: the withdrawal of artificial food and fluid from terminally ill patients. A sample of 160 Japanese nurses, who completed a questionnaire that included forced-choice and open-ended questions, supported this act under only two specific conditions: if the patient requested it, and if it relieved the patient’s suffering. They considered that the doctor’s orders, the family’s request, or the patient’s advanced age did not ethically justify this act. A small number of people who had recently lost a relative took part in semistructured interviews focusing on their experiences of their terminally ill relatives being given artificial food and fluid. Ethical, social and cultural factors surrounding this issue are discussed.